The Effect of Different Angiolytic Lasers on Resolution of Subepithelial Mucosal Hematoma in an Animal Model. (June 2014) - Novakovic, Daniel; D'Elia, Joanna; Branski, Ryan C.; Blitzer, Andrew
Objective: Vocal fold hematoma is traditionally managed with a period of voice rest, in the order of weeks, to allow natural resolution. This study is designed to examine the efficacy and safety of a number of hemoglobin-avid (vascular) lasers when used in the setting of acute vocal fold hematoma. Methods: Venous blood drawn from 4 white rabbits was used to create an array of subepithelial hematomas in the buccal cavities of each animal. Laser energy from 1 of 3 different lasers (532-nm pulsed potassium titanyl phosphate [KTP], 532-nm diode KTP, and 940-nm diode laser) was applied to each of the test hematomas at varying energy levels. Hematoma sites were photographed at days 0, 1, 5, 7, 9, and 12. Two animals were sacrificed on day 7 and the remainder on day 12. Histological evaluation of collateral tissue damage and residual hematoma was performed on biopsy specimens. Results: Macroscopic and microscopic ulceration at laser-treated sites was mostly resolved by day 7. Inflammatory cell infiltrate was present in laser-treated and hematoma-only sites. Laser-treated samples showed alterations in vascularity. Conclusion: Hemoglobin-avid lasers may be beneficial in accelerating subepithelial hematoma resolution with a favorable tissue damage profile.